HUBUNGAN DIABETES MELITUS TIPE 2 DENGAN KUALITAS TIDUR - Aritonang, Sriulina; Siahaan, Jekson; Siagian, Laura (Universitas Methodist Indonesia, 2020)
ABSTRACT Background : Based on data from the International Diabetes Federation (IDF), it was found that 207 million people in the world suffer from DM. The number continues to increase in 2019, there are 415 million people in the world who suffer from DM. This shows that DM sufferers in the world continue to increase every year. DM is a group of metabolic diseases characterized by hyperglycemia due to impaired insulin secretion, insulin action, or both. DM can be classified into several types, namely, type I DM, type 2 DM, gestational DM, and other types of DM. There are several types of DM, type 2 DM is the type most commonly found in 90-95%. Patients with DM usually feel discomfort as a result of the symptoms of the disease. The symptoms, such as: polyuria (lots of urine), polydipsia (drink a lot), poliphagi (a lot of eating), and others that occur at night can certainly interfere with sleep. The occurrence of sleep disturbances will have an impact on increasing the frequency of awakening, difficulty falling back to sleep, sleep dissatisfaction which ultimately results in a decrease in sleep quality. The purpose of this this study was to determinan the relationship between type 2 diabetes mellitus and sleep quality. Method : The research method used is a Literature Review, using secondary data. Data were collected using documentation techniques. The research journals used were 5 journals with inclusion criteria for the language used was Indonesian, with the research subjects of the type 2 DMpatients, and full text publication. Conclusion : There is a relationship between type 2 diabetes mellitus and sleep quality and the realitionship between sleep quality and KGD, HbA1c, blood pressure, BMI and sociodemography. Keywords : DM type 2, Sleep quality.